Gender Differences in the Development of Other-Regarding Preferences - Katrin John; Stephan L. Thomsen (Institute of Labor Economics (IZA), 2017)
We use data from a gender-neutral dictator and public goods game setting to analyze differences in other-regarding preferences between boys and girls aged 10 to 17. The results indicate a higher mean of dictator giving, degree of egalitarian decisions and lower frequency of selfish decisions, free-riding and efficiency concerns for girls. Gender differences are already established at approximately age 10. They cannot be explained by gender-specific increases in other-regarding preferences, differences in dispositions or the impact of personality traits. We conclude that genes and early social learning are the sources of gender differences in other-regarding preferences.
Keywords: C91; D03; J16; 330; gender; other-regarding preferences; personality traits; dictator game; public goods game